The Influence of Tourism Object Development on the Socio-Economic Conditions of the People of Karampuang Island, Mamuju Regency - Afridayanti Afridayanti (Income Journal Of Economics Development, 2022)
This study aims to determine the Development of Tourism Objects on the Social Economic Impact of the Karampuang Island Community in Mamuju Regency. The theoretical basis in this research includes the Development of Tourism Objects and the Social Economic Impact of the Karampuang Island Community. This type of research used in this research is quantitative research methods. The data collection technique used a questionnaire. The data analysis technique used is validity test, reliability test, simple regression analysis, determination coefficient (R) and partial test (t test). The results showed that based on the results of the t test, the Tourism Object Development variable had a positive and significant effect on the Social Economic Impact of the Mamuju Regency Community and the magnitude of the correlation or relationship value (R) was 0.706. Obtained the output coefficient of determination (R Square) of 0.699 which implies that the influence of the independent variable of Tourism Object Development on the dependent variable of the Socio-Economic Impact of the Karampuang Island Community is 69.9%.